Calidad molinera de las principales variedades de arroz (Oryza sativa L.) que se comercializan en nuestro país. - Medina Piza, Jilson Antonio (2022)
The objective of this research work is to collect information on the milling quality of the main varieties of rice (Oryza sativa L.) that are marketed in our country. The milling quality of the current varieties in the trade of our country will be analyzed and determined. In this research work, the results of some projects on the genetic improvement of rice, the release of improved varieties and their milling quality, carried out by agricultural research institutes and laboratories in the country, have been cited. The milling quality of each of the varieties of rice cited in this work will be determined, a brief description of the industrial conditions that they must have for their commercialization, the characteristics that the polished grain required by the consumer must have. However, the different quality properties of the rice grain are due to the genetically improved seed variety. However, these properties tend to be affected by adverse climate factors and poor practices in crop management. It was determined that the milling quality of the current varieties in the Ecuadorian trade have very good milling, commercial and culinary characteristics, it is also worth mentioning the importance of adopting new varieties, which, in general, have good milling and culinary quality.